Effects of body position, hyperinflation, and blood gas tensions on maximal respiratory pressures in patients with chronic obstructive pulmonary disease. - Heijdra, Y. F. (1994)
BACKGROUND--Inspiratory muscle strength in patients with chronic obstructive pulmonary disease (COPD) can be affected by mechanical factors which influence the length of the diaphragm, and by non-mechanical factors. The aim of the present study was to evaluate firstly the effects of body position on respiratory pressures and, secondly, to determine the relative contribution of age, body mass index (BMI), lung volumes, and arterial blood gas tensions to respiratory muscle strength. METHODS--Thirty male patients with stable COPD (mean FEV1 40.4% predicted) participated in the study. Maximal inspiratory and expiratory mouth pressures (PImax, PEmax) and maximal inspiratory transdiaphragmatic pressures (PDI) in the sitting and supine position, lung function, and arterial blood gas tensions were measured. RESULTS--Mean (SD) PImax in the sitting position was higher than in the supine position (7.1(2.3)kPa v 6.4(2.2)kPa respectively). In contrast, PDI in the sitting position was lower than in the supine position (10.0(3.5)kPa v 10.8(3.7)kPa respectively). PEmax was higher in the sitting position (9.3(3.0)kPa) than in the supine position (8.7(2.8)kPa). Significant correlations were found between inspiratory muscle strength on the one hand, and lung function parameters, BMI, and arterial blood gas tensions on the other. CONCLUSIONS--Inspiratory muscle strength in patients with COPD is influenced by mechanical factors (body position, lung volumes) and non-mechanical factors (BMI, FEV1, and blood gases). PImax and PEmax are lower in the supine position while, in contrast to healthy subjects, PDI is higher in the supine position than in the sitting position.